Evaluating an EFL Textbook: To What Extent Does The 2013 Curriculum-Based Textbook Accomplish Pedagogical Aspects? - Nimasari, Elok Putri (Proceeding of International Conference on Teacher Training and Education, 2016)
According to Permendikbud number 71 year 2013 article 1, the government provides guide books for learning process, so pilot project schools for the 2013 curriculum must use the textbooks developed by the government. The 2013 curriculum-based English textbook for grade X is entitled âBahasa Inggrisâ (BI hereafter). Since the use textbook is so significant and no textbook is completely accurate, this present study aims to verify: (1) how the 2013-based curriculum textbook âBahasa Inggrisâ (BI hereafter) for grade X of senior high school accomplishes pedagogical aspects; (2) the studentsâ responses toward BI textbook for grade X. It is classified as a qualitative study. BI textbook for grade X is the object of the study while SMA 1 Ponorogo and SMA Muhammadiyah 1 Ponorogo are the setting of the study. Document analysis, personal interview, and focus group discussions are the data collection techniques and the instruments are a constructed criteria rubric to analyze the textbook and two lists of interview. After analysis of data, it is found that BI textbook has strengths in aspects of methodology, presentation, design, and learnerâs factors and weaknesses in aspects of content coverage and material completeness. Moreover, BI textbook is sufficiently beneficial and challenging for the students.